Extitutions and security: movement as code - Tirado, Francisco; Domenèch, Miquel (Informática na educação teoria & prática, 2013)
How can we guarantee the security of our means of transport? How can we strengthen that of our communications? How can we keep our ideology or our market safe? Etc. In this context, the press has recently been asking whether it is possible to be 100% certain that a person is not concealing a dangerous item on passing through an airport control. Nonetheless, technical solutions may be about to alter the aforementioned scenario. Indeed, the authorities in a number of countries have decided to install scanners at airports that allow people to be completely undressed without having to remove their clothes. The protests which have been voiced, quite reasonably, against this measure have been completely stifled by arguments based on security. Just a glance at the press in any European country in the last few days will confirm this affirmation. The example of scanners has not been a random choice to begin this article. It has to do with the fact that airports are truly a unique place to illustrate one of the most characteristic phenomena of our current societies: the need to manage mobility and security in unison. However, from our point of view security is much more than an excuse for legitimising procedures for surveillance and control, or a characteristic feature of contemporary states. It constitutes the very logic of such states. It is characterised by circulation and movement, and it operates as an authentic code that is capable of generating new forms of sociality and regimes of power.